Analisis Penerimaan Crypto Aset di Kalangan Mahasiswa di Batam - Suwarno, S; Saputra, Indra (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Cryptocurrency is defined as a digital currency that uses cryptography that is used for investing or buying and selling assets. Every transaction made with cryptocurrencies will be stored in blockchain technology. Knowing that cryptocurrency users are relatively very large, this shows a very high interest in crypto asset investment, it's just that there is a lack of research on the factors that influence the acceptance of crypto asset investment among students, especially University at Batam. This research aims to be able to provide information regarding the factors that influence students in Batam who accept the use of crypto asset investments. This study uses a multi method, namely quantitative and qualitative methods which will be used as a comparison of study results at the end of the study. The model used in this research is the TAM (Technology Acceptance Model). The population of this study included students from 5 tertiary institutions with a total of 7.226 students and the number of samples used was 100 students in Batam for quantitative method and 10 students for qualitative method. Data from questionnaires and interviews obtained were then analyzed separately and a comparison was made of the factors that influence acceptance of crypto assets among students in Batam. The results showed that based on the results of the two studies, the attitude variable had a significant effect on the behavioral intention variable, the perceived usefulness variable had a significant effect and the perceived ease of use had an insignificant effect on the attitude variable.